Analisis Standar Penilaian Pendidikan di Indonesia ( Komparasi Permendikbud No. 21 Tahun 2022 dan Permendikbud No. 23 Tahun 2016 ) - yunianto, Teguh; Pradana, Dhimas Rega (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract This study aims to conduct a comparative analysis between the Regulation of the Minister of Education and Culture (Permendikbud) Number 21 of 2022 and the Regulation of the Minister of Education and Culture Number 23 of 2016 concerning educational assessment standards in Indonesia. This type of research is a literature study. Literature study is a series of activities related to the method of collecting library data sourced from journals, books, and other documents related to theories and information, both past and present, related to the topic being studied. The focus of the research includes the scope of assessment, assessment objectives, assessment procedures, and the selection and development of assessment instruments. The results of the research Permendikbud No. 21 of 2022 regulate student assessment standards and elements created in the learning process. Objectively, fairly, and educatively, evaluation of student learning outcomes is carried out, while Permendikbud No. 23 of 2016 concerning Educational Assessment Standards. From the applicable regulations, that the Assessment of Primary and Secondary Education is carried out by Educators, Educational Units, and by the Government. While the aspects assessed are the attitude aspect (consisting of spiritual and social attitudes), knowledge aspect and skills aspect.